MOOD AND MODALITY IN SOEKARNO’S 1955 SPEECH - Syamsidar Syamsidar; Ika Yatmikasari; Dian Nurrachman (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This research deals with the interpersonal meaning of Soekarno’s speech in the first 1955 Asian-African Conference. The study focuses on analysing mood types and choice of modality in that speech. As the speech brought the theme of spirit of solidarity and brotherhood, then this study aims at examining how the choice of mood types and modality represent this theme. To realize this, the framework of Systemic Functional Linguistic (SFL), particularly on mood and modality system by Halliday and Mathiessen (2004), is employed. From the discussion, it is found that clauses are mostly categorized as declarative clauses. It proves that the Asian-African Conference was held by the realization of solidarity and brotherhood. The use of declarative clauses indicates the speaker’s competences in delivering persuasive speeches by conveying factual information. In addition, it is found that the speaker is neutral and seems to have close relation with the audience. Meanwhile, the use of low degree of modality is helpful to encourage the audience’s confidence to act together.